1988
DOI: 10.1016/0092-8674(88)90115-8
|View full text |Cite
|
Sign up to set email alerts
|

ProOmpA is stabilized for membrane translocation by either purified E. coli trigger factor or canine signal recognition particle

Abstract: We have isolated large amounts of E. coli outer-membrane protein A precursor (proOmpA). Purified proOmpA is active in membrane assembly, and this assembly is saturable with respect to the precursor protein. A proOmpA-Sepharose matrix allows affinity isolation of trigger factor, a soluble, 63,000 dalton monomeric protein that stabilizes proOmpA in assembly competent form. Comparison of trigger factor's amino-terminal sequence with those in a computer data bank and with those encoded by sec genes, as well as gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 38 publications
5
156
1
Order By: Relevance
“…All other chemicals were purchased from Sigma (St Louis, MO, USA). SecA, 38 SecB 39 and proOmpA 40 were purified essentially as described. GST, GST-SecY(Tyr332-Tyr365) and GST-SecY (Phe170-Gly184) were purified with glutathione-Sepharose 4B according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…All other chemicals were purchased from Sigma (St Louis, MO, USA). SecA, 38 SecB 39 and proOmpA 40 were purified essentially as described. GST, GST-SecY(Tyr332-Tyr365) and GST-SecY (Phe170-Gly184) were purified with glutathione-Sepharose 4B according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that TF has a binding affinity to this protein when going from a denaturant like urea to renaturation conditions by either dilution or dialysis [2]. Therefore, stoichiometric complexes of TF and proOmpA could be isolated [2,3]. Using genetically engineered strains of E. coli either over-or underproducing TF, however, the membrane transport of proOmpA was not affected [4].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Lep75-RNCs bound TF with low affinity as vacant ribosomes, indicating that TF does not interact with the hydrophobic signal-anchor sequence of Lep. However, given the high concentration of TF in the cell (about 50 mM total 30 ), TF can probably bind to most ribosomes, including non-translating ribosomes and RNCs, even to those RNCs that do not present a TF-binding motif. This raises the question of how the other RPBs gain access to the nascent peptide for N-terminal processing (PDF, MAP) and membrane targeting (SRP).…”
Section: Kinetics Of Tf Interaction With Non-translating Ribosomesmentioning
confidence: 99%